Convergence in West German Regional Unemployment Rates - Christian Bayer; Falko Juessen (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 2006)
Differences in regional unemployment rates are often used to describe regional economic inequality. This paper asks whether changes in regional unemployment differences in West Germany are persistent over time. Understanding the persistency of regional unemployment differences helps us to asses how effective regional policy can be. While univariate tests suggest that changes in unemployment differences are persistent, more powerful panel tests lend some support to the hypothesis that regional unemployment rates converge. However, these tests reveal a moderate speed of convergence at best. Since there is a structural break following the second oil crisis, we also employ tests that allow for such a break. This provides evidence for both, convergence and quick adjustment to an equilibrium distribution of regional unemployment rates that is subject to a structural break.
Keywords: J60; R23; 519; stochastic convergence; unemployment; structural break; unit root